The ‘Sirmium Group’ – an overview - Faltin, Dirk (KOINON: The International Journal of Classical Numismatic Studies, 2019)
In recent years, a significant number of small silver coins from south-eastern Europe have come to light. These coins were minted in 6th century Sirmium (today’s Sremska Mitrovica in Serbia) and they come in two denominations, which we refer to as quarter- and half-siliquae. The intended weights seemed to have been about 0.9 grams for the quarter-siliquae and about 1.8 grams for the half-siliquae.